Penerapan Prinsip Good Governance terhadap Masalah Sertifikat Ganda oleh BPN Kota Padang - Putra, Bintang Pratama; Putri, Nora Eka (Department of Political Science - Universitas Sains Al-Qur’an, 2025)
Duplicate land titles remain a critical land issue in Indonesia, causing legal uncertainty and undermining public trust. This study examines how the Padang City National Land Agency (BPN) applies good governance principles—transparency, accountability, and work effectiveness—in addressing these cases. Using a descriptive qualitative method with interviews, observations, and documentation, the study finds that BPN's efforts, including digital tools such as the Sentuh Tanahku application and Bhumi website, have not been fully effective. Key challenges include incomplete land data, limited public digital literacy, and weak internal coordination. The findings highlight the need for integrated digital governance and improved service responsiveness to resolve land title conflicts and enhance public trust.